Open Surgery vs. Endovascular Repair of Abdominal Aortic Aneurysms: A Systematic Review - João Filipe Vieira Lopes Pereira,; Kuezia Da Veiga Gonzales Serra,; Nivea Kayle Cardoso de Araújo,; Ana Quézia Gonçalves Pereira,; Bárbara Maria de Couto Almeida Diniz,; Bianca Garcia Jacques,; Cícera Fernanda Paes de Oliveira,; Josefa do Nascimento de Lima,; David Moreira Sampaio,; Deyvid Abade de Castro Souza,; Diogo Mariano Hildefonso,; Eric Alves Pereira Silva,; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Endovascular repair (EVAR) and open surgical repair (OSR) are the primary approaches for treating abdominal aortic aneurysms (AAA). Both techniques present unique risks and benefits across short-, medium-, and long-term outcomes. EVAR, being less invasive, is associated with lower perioperative mortality and morbidity rates but carries an increased risk of secondary rupture and reinterventions. Conversely, OSR, although more invasive, demonstrates lower rates of late complications and reinterventions. This study aims to comprehensively analyze and compare the perioperative complications and long-term survival outcomes of these two interventions. To analyze perioperative complications and long-term survival rates associated with endovascular repair and open surgical repair in the management of abdominal aortic aneurysms. A systematic review was conducted using the Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMed), and MEDLINE databases. Predefined inclusion and exclusion criteria were applied, and relevant articles were identified using the keywords “Endovascular repair,” “Open surgery repair,” “Abdominal aortic aneurysm,” and “Complications,” combined with the Boolean operator “AND.” Comparative analysis of EVAR and OSR reveals that EVAR offers lower perioperative mortality and faster recovery but is associated with a higher risk of long-term complications and reinterventions. On the other hand, OSR, despite its invasive nature and higher short-term mortality, is linked to fewer late complications and reinterventions. Both approaches exhibit similar mortality rates over the long term. Therefore, the choice of treatment should be individualized based on the patient’s clinical profile and preferences. EVAR and OSR are equally effective in managing AAA, with differences primarily in perioperative and long-term outcomes. EVAR minimizes perioperative risks but requires ongoing monitoring for late complications, while OSR, though more invasive, offers greater long-term stability with fewer late reinterventions. The choice between these methods should prioritize patient-specific factors and preferences.